Sistema de navegación para personas con discapacidad visual en espacios cerrados utilizando realidad aumentada (2023)
Visual impairment refers to impairment of vision that can result in partial or total loss of the ability to see. In Colombian educational settings, students with this condition face challenges in navigating indoor spaces due to the lack of braille signage. This work details the development, implementation and testing of a mobile application based on Augmented Reality (AR) that uses rMQR codes to provide sound descriptions of locations